Function of Ltbp-4L and fibulin-4 in survival and elastogenesis in mice - Insa Bultmann-Mellin; Jeroen Essers; Paula M. van Heijingen; Harald von Melchner; Gerhard Sengle; Anja Sterner-Kock (The Company of Biologists, 2016)
LTBP-4L and LTBP-4S are two isoforms of the extracellular matrix protein latent-transforming growth factor beta-binding protein 4 (LTBP-4). The mutational inactivation of both isoforms causes autosomal recessive cutis laxa type 1C (ARCL1C) in humans and an ARCL1C-like phenotype in Ltbp4−/− mice, both characterized by high postnatal mortality and severely affected elastogenesis. However, genetic data in mice suggest isoform-specific functions for Ltbp-4 because Ltbp4S−/− mice, solely expressing Ltbp-4L, survive to adulthood. This clearly suggests a requirement of Ltbp-4L for postnatal survival. A major difference between Ltbp4S−/− and Ltbp4−/− mice is the matrix incorporation of fibulin-4 (a key factor for elastogenesis; encoded by the Efemp2 gene), which is normal in Ltbp4S−/− mice, whereas it is defective in Ltbp4−/− mice, suggesting that the presence of Ltbp-4L might be required for this process. To investigate the existence of a functional interaction between Ltbp-4L and fibulin-4, we studied the consequences of fibulin-4 deficiency in mice only expressing Ltbp-4L. Resulting Ltbp4S−/−;Fibulin-4R/R mice showed a dramatically reduced lifespan compared to Ltbp4S−/− or Fibulin-4R/R mice, which survive to adulthood. This dramatic reduction in survival of Ltbp4S−/−;Fibulin-4R/R mice correlates with severely impaired elastogenesis resulting in defective alveolar septation and distal airspace enlargement in lung, and increased aortic wall thickness with severely fragmented elastic lamellae. Additionally, Ltbp4S−/−;Fibulin-4R/R mice suffer from aortic aneurysm formation combined with aortic tortuosity, in contrast to Ltbp4S−/− or Fibulin-4R/R mice. Together, in accordance with our previous biochemical findings of a physical interaction between Ltbp-4L and fibulin-4, these novel in vivo data clearly establish a functional link between Ltbp-4L and fibulin-4 as a crucial molecular requirement for survival and elastogenesis in mice.